1992
DOI: 10.1128/iai.60.10.4394-4401.1992
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic infections and retrovirus-induced immunodeficiency: studies of acute and chronic infections with Toxoplasma gondii in mice infected with LP-BM5 murine leukemia viruses

Abstract: Mice infected with LP-BM5 murine leukemia viruses develop a syndrome, termed mouse AIDS (MAIDS), characterized by increasingly severe immunodeficiency and progressive lymphoproliferation. Virus-infected mice were examined for the ability to resist acute infection and to control chronic infection with the protozoan Toxoplasma gondii, a major opportunistic pathogen of individuals infected with human immunodeficiency virus. Mice infected with the retroviruses for 2 or 4 weeks responded normally to challenge with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 37 publications
5
30
1
Order By: Relevance
“…Spleen and inguinal lymph node weights in co-infected mice were markedly reduced compared to mice infected with the virus only. This phenomenon had been described in models of co-infection with LP-BM5 MuLV and Toxoplasma godii [18,19] and Leishmania major [32]. In contrast to the study by Gazzinelli et al [IS], we found no change in the ecotropic viral load, or in Con A-induced spleen cell proliferation in vitro.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Spleen and inguinal lymph node weights in co-infected mice were markedly reduced compared to mice infected with the virus only. This phenomenon had been described in models of co-infection with LP-BM5 MuLV and Toxoplasma godii [18,19] and Leishmania major [32]. In contrast to the study by Gazzinelli et al [IS], we found no change in the ecotropic viral load, or in Con A-induced spleen cell proliferation in vitro.…”
Section: Discussioncontrasting
confidence: 94%
“…Another possibility is that MAIDS, which is responsible for the increased expression of some proinflammatory cytokines [27,28], could accentuate the inflammatory response to C. neoformans, resulting in increased mortality through pulmonary and cerebral oedema. 18 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The report published in this issue of the European Journal of Clinical Investigation [24] provides additional evidence that combination of anti-inflammatory, antiretroviral and lympholytic therapies may lead to total viral suppression and restoration of immune function in a murine model of AIDS. Infection of mice with retroviral complex LP-BM5 leads to profound immunodeficiency, characterized by impaired T-and B-cell responses to mitogens, polyclonal B-cell activation, hypergammaglobulinemia, enhanced susceptibility to secondary infections, and the emergence of lymphomas due to the development of anergy [25]. Fraternale and colleagues treated LP-BM5 infected animals with GSH-loaded erythrocytes (antioxidant effect) and the reverse transcriptase inhibitor AZT (antiviral effect), or this combination alternating with fludarabine.…”
mentioning
confidence: 99%